My trip to al-Qaeda [videorecording (DVD)] : behind the scenes of the War on Terror - Gibney, Alex; Gibney, Alex; Mosher, Gregory; Wright, Lawrence, 1947- (Docuramafilms : Distributed in the U.S. by New Video, 2012)
"In 2006, Pulitzer Prize-winning journalist Lawrence Wright staged "My Trip to al-Qaeda," a one-man play that explored the moral dilemmas he encountered while researching his bestselling book, "The Looming Tower: al-Qaeda and the Road to 9/11." Culled from more than 600 interviews and 4,100 pages of notes, the play integrated his journalistic insights with personal stories, live footage, and photos of the places he visited during his extensive research. In My Trip to al-Qaeda, Academy Award winner Alex Gibney (Taxi to the Dark Side) brings Wright's performance to the big screen and chronicles his quest to understand the history and the modern incarnation of radical Islamic terrorism. Through Wright's probing efforts to come to terms with his and his country's role in the chain of events that led to 9/11, My Trip to al-Qaeda sheds crucial light on terrorism, Islam and America." -- Container.